Circular RNA circ_0096041 promotes osteosarcoma cell proliferation and migration via sponging miR-556-5p and regulating LIN28A expression: circ_0096041 promotes osteosarcoma cell proliferation - Zhou, Fulin; Wu, Hao; Yin, Zhen; Zhou, Weibo; Chen, Wei (Cellular and Molecular Biology, 2024)
Strategies targeting lin-28 homolog A (LIN28A) for the treatment of osteosarcoma are limited, even though salient findings have illustrated the crucial role of LIN28A in bone deformities and cancer. In the present study, we proved circ_0096041, one of the circular RNAs (circRNAs) with significant upregulated expression in osteosarcoma, to be notably engaged in the progression of osteosarcoma. We elucidated that osteosarcoma patients with highly expressed circ_0096041 had relatively worse prognoses. We determined that circ_0096041 potentially sponge miR-556-5p using the Circular RNA Interactome database. Meanwhile, we proved circ_0096041 was associated with miR-556-5p. Furthermore, we determined that miR-556-5p was targeted by LIN28A directly, evidenced by in silico analysis using the miRWALK tool and in vitro analysis. Functionally, our experimental setting aimed to explore the function of circ_0096041/miR-556-5p/LIN28A axis in vitro and in vivo. Our findings demonstrated that circ_0096041 boosted the proliferation and migration of osteosarcoma via LIN28A/miR-556-5p axis. In vivo models were further established to estimate the metastasis promoted by circ_0096041. This research elucidated the enhanced osteosarcoma progression by circ_0096041 and its potential mechanism, which provided innovative targets for osteosarcoma treatment.